Experimental Study of Concrete Using Raw Rice Husk as Partial Replacement of Cement with Natural Fiber (Jute Fiber) as Reinforcing Material - Sristi Das Gupta (Pouyan Press, 2021)
The release of GHG, radioactive metals and other chemicals is detrimental to the environmental impact of cement manufacturing. The use of natural pozzolan (raw rice husk) as a partial substitute of cement in concrete may not only serve to increase compressive strength but also be environmentally sustainable. This paper manages the idea of utilizing Rice Husk as a partial substitution of cement and non-metallic natural fibers (Jute fiber) in concrete to develop an FRC material to study the possible improvement in the 28-day strength and also to reduce the plastic shrinkage crack. Different compositions of 13mm jute fiber (0.1%, 0.2%, and 0.3%) and Rice Husk (5%, 10%, and 15%) were added to concrete with a water-cement ratio of 0.38 in this study. It depicts that the compressive strength improves by up to 2.03% relative to plain concrete after using both jute fibers and rice husk. Further addition of fiber and rice husk prompts a diminishing pattern in strength as the two substances increased, the compressive strength gets diminished, causing low workability of concrete. Moreover, Shrinkage tests were performed to assess the existence of shrinkage cracks; it indicates that when applying jute fiber, the shrinkage crack region decreases. The optimum content of jute fiber is 0.2% (13mm) and rice husk is 10% for the maximum increment of compressive strength. However, the incorporation of 0.3% jute fibers with 13 mm length was found to be very effective in suppressing shrinkage cracks to near zero